Compare the effectiveness of two treatments, behavioral activation and acceptance and commitment therapy, on depression and mental rumination in mothers of children with cerebral palsy in Ilam city - Mostafa Alirahmi; Sattar Kikhavani; Homeira Soleimannejad (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Since in most families, mothers are more responsible for taking care of children and have more responsibility than fathers for monitoring the child, taking care of a disabled child can have a more negative effect on the psychological state of mothers. This study aimed to investigate the effectiveness of behavioral activation (BA) and acceptance and commitment therapy (ACT) in depression and rumination in mothers with children with cerebral palsy. MATERIALS AND METHODS: This research was quasi-experimental field research with a pre-posttest and control group. The study population comprised 237 mothers with children who had cerebral palsy and were referred to occupational therapy centers in Ilam, Iran. The sample consisted of 60 participants selected by convenience sampling, who were randomly divided into two experimental groups (BA and ACT) and a control group (n = 20 per group). Data were analyzed using Statistical Package for the Social Sciences (SPSS) version 27.0 with descriptive and inferential statistics, such as mean, standard deviation, and multivariate analysis of covariance (MANCOVA). RESULTS: The results of both BA and ACT were effective in reducing depression (P < 0.01) and rumination (P < 0.01) in the two experimental groups compared with the control group in the posttest phase. Furthermore, the effectiveness of the ACT in reducing depression and rumination was found to be more significant than the effectiveness of BA (P ≤ 0.05). CONCLUSION: The findings of the study suggest that both BA and ACT are effective in reducing depression and rumination in the research participants. However, the study also found that ACT was more effective than BA in reducing depression and rumination. Thus, both approaches can be used to strengthen treatment interventions to lessen depression and rumination in the research participants.